Relacyjne podejscie do percepcji wzrokowej na przykladzie zawodników specjalizujacych siê w grze w pilke reczna - Machnaz, W. (Human Movement, 2001)
In physical culture there are sports or areas of sporting activity in which the process of reception of signals from the environment has direct consequences for the effectiveness of activities. For example, ball games, because of rapid changes of situations, require that the participants make constant perceptive assessments based, first of all, on visual signals. Through an optic analyser the participant receives information about his/her own movements, external conditions and opponents' and partners' behaviour. Since visual control of the game is indispensable, we can assume that any distortions of the function of sight will impair the results of most activities of the player. Eliminating the visual control by for example closing the eyes basically makes it impossible to participate in the game. Therefore, we can arrive at a conclusion that seeing has great significance in ball games and must be treated as a fundamental factor which cannot be replaced or ignored. However, there is scarcity of empirical examinations concerned with the quality of reception and processing of information by players specialising in games. That fact may result from treating this activity as something obvious as it is done effortlessly and as if automatically. It is worth noticing that these problems have been tackled by research workers from ZGS Department at AWF in Wroclaw (University of Physical Education in Wroclaw). As early as in the 1960s Szymanski [13, 14] wrote about the significance of central and peripheral vision and divisibility of attention in the process of learning games. Azman-Zielinska et al. [1] proved that the size of the vision area is affected by, among others, sex and characteristics of a sport discipline. Dziasko [3] stated that football players perceived more quickly and more exactly than people not connected with sport. Machnacz [8] further proved the existence of significant differences in the level of perceptive orientation both between sportsmen of various sports disciplines and sportsmen and non-sportsmen at a young age. In Naglak's opinion [10], technique in disciplines characterized by open habits is based on perceptive and mobile activities previously memorized; therefore, for the player the first step (introduction) to any activities with the ball should be becoming aware of the situation and thinking towards the method of achieving the goal. The aim of the research was to determine relations (relationships between values) existing in the speed and exactness of perception among players specialising in handball according to age, sex and the level of sports skills. The research comprised a group of 77 players, that is 40 female and 37 male who specialised in handball, and also a similar group of non-sportsmen. All the players took part in central training on the level of team representing Lower Silesia District in the group age of younger teenagers (ML) and younger juniors (JM). To assess the characteristic features of perception - speed and precision, we employed a standard test elaborated by Pracownia Psychomotoryczna PAN (Psychomotoric Institute of Polish Academy of Science) - Grymsley, Ruch and Warren test [6, 12]. The final results were expressed by indicators elaborated by means of the following methods: 1. Basic assessment of speed and precision of perception (the D-Z difference). 2. This assessment is multiplied by the relevant weight. In case of WSK2 this weight is the expression (1-Z/D) which makes the factor sensitive when there are many wrong answers. 3. In case of WSK 3 the weight is the quotient (D/150) which is the proportion of good answers to the number of all possible answers. The elaborated versions of indicators have the following variants: WSK1 = D-Z, WSK2 = (D-Z)(1-Z/D), WSK3 = (D-Z)(D/150), where: D - the number of good answers, Z - the number of wrong answers. The results were elaborated in the form of average percentage put in tables in particular variants. The analysis of the conducted research allowed us to formulate the following conclusions: 1. In all the analysed sports groups, the most advantageous level of speed and precision of perception could be observed with younger juniors (JM). 2. All of the sports groups (S) achieved much better results, which prove higher speed and precision of perception, when compared with control groups (G). The difference was over 13%. 3. With the female participants, the level of perception does not differentiate the older group from the younger group, whereas the older boys are much better than the younger ones. 4. The image of sexual dimorphism is not uniform. In the younger group the boys proved to be better, whereas in the older one girls were better. 5. Sports competition turned out to be a positive factor affecting the increase in the effectiveness of perception. As a result of 'match tiredness' we could notice an improvement in the level of perception by over 8%. 6. Players from the basic team (P) achieved better results than their replacements (R) by circa 13%. It may be evidenced that visual perception facilitates the level of sports skills in the game of handball. 7. The level of perception does not differentiate the players according to the position occupied in the game.